Comparison of Live Coral Cover in Central and South Bangka - Mu'alimah Hudatwi; Umroh Umroh (Universitas Diponegoro, 2018)
Coral reef ecosystem has many biological, ecological, and economical functions to the universe. This ecosystem provides shelter, food, and home for many marine organisms and together they perform diverse and rich ecosystem. However, this diverse ecosystem is very susceptible to environmental change, such as climate change, ocean acidification, and other anthropogenic impact. When reef-building coral could not stand with harsh condition they will eventually die. We assume that anthropogenic stressor such as turbidity, terrestrial runoff, and sedimentation is the main problem here, because of high number of tin mining activities. Bangka and Belitung Islands are huge tin producer and has been exploited heavily by the legal and illegal miner company. The purpose of this study is to investigate the live coral cover in Central and South Bangka by using the line intercept transect to calculate the live coral, died coral, and algae in each stations. The results showed that the coral cover in Central Bangka and South Bangka has fair condition (25-40% of live stony coral). Value of live and dead coral cover was 40% with Semujur and Ketawai represent the coral cover in Central Bangka. While South Bangka has slight (1-2%) difference of live coral, dead coral, and algae cover. High number of dead coral mainly composed by dead coral overgrown by algae, allegedly caused by high turbidity and sedimentation from the anthropogenic stressor. Ekosistem terumbu karang mempunyai fungsi biologi, ekologi, dan ekonomi yang bermanfaat bagi manusia. Ekosistem ini menyediakan tempat berlindung, makanan, dan rumah bagi organisme laut dan membentuk suatu ekosistem yang kaya dan beragam. Namun, ekosistem ini sangat rentan terhadap perubahan lingkungan, sepertiiklim, asidifikasi, dan dampak lain yang dilakukan manusia. Ketika terumbu karang tidak mampu bertahan dengan perubahan lingkungan yang ekstrim mereka akan mati. Kami menduga bahwa dampak antropogenik seperti turbiditas, runoff dari darat, dan sedimentasi merupakan penyebab utama kerusakan terumbu karang, karena banyaknya aktivitas penambangan. Kepulauan Bangka belitung adalah penghasil timah terbesar dan telah dieksploitasi oleh penambang timah legal maupun ilegal. Tujuan dari penelitian ini adalah untuk mengetahui tutupan karang hidup di Provinsi Bangka Tengah dan Bangka Selatan dengan menggunakan metode traksek garis. Hasil menunjukkan bahwa terumbu karang di Bangka Tengah dan Selatan termasuk kategori sedang (25- 40% tutupan karang). Tutupan karang hidup dan karang mati di Bnagka Tengah sebesar 40% dari hasill pengamatan di Semujur dan Ketawai. Sedangkan nilai tutupan karang hidup, karang mati, dan alga di Bangka Selatan mempunyai angka perbedaan yang rendah (1-2%). Tingginya tutupan karang mati tersusun oleh karang mati yyang ditumbuhi alga yang disebabkan oleh turbiditas dan sedimentasi.